Forward Kinematics Solution Analysis of 3-CRS/SP Parallel Mechanism based on BP Neural Network Algorithm - Zhao Yaohong; Xia Hao; Wang Ziqian; Li Ruiqin; Yao Yinyin; Wang Yongjun (Jixie chuandong)
A method for solving the forward kinematics analysis of parallel mechanism based on BP neural network is presented. According to the algorithm of BP neural network,three layers forward neural network is adopted. The inverse kinematics solution of the mechanism can be obtained by establishing the rotation matrix of3-CRS/SP parallel mechanism. It can be used as input of neural network and the dynamic platform position including four parameters can be regard as the output,then neural network can be trained. The simulation and experimental results show that the method is fast and effective for solving the parallel mechanism forward kinematics,and it is intuitive and simple compared with the analytical method. It can provide numerical reference for the control process of parallel mechanism.